Ophthalmic herpes zoster secondary to intrauterine varicella. - Betiu, M.; Iacovleva, I.; Chiriac, A.; Sturza, V. (European Journal of Pediatric Dermatology, 2018)
Few cases of herpes zoster in infants caused by maternal varicella during pregnancy have been reported.We present a case of a 5-month-old child diagnosed and treated for ophthalmic herpes zoster secondary to maternal infection with Varicella-Zoster Virus during the third trimester of pregnancy.